THE ADMINISTRATIVE JUSTICE OF THE REPUBLIC OF KAZAKHSTAN AS AN INSTRUMENT AND SUPPORT OF THE HEARING STATE - Balieva Загипа Яхяновна; Ayupova Зауре Каримовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
As we know, administrative justice is a kind of legal institution of judicial protection necessary to restore violated subjective rights, freedoms of citizens, legitimate interests of legal entities and other organizations by monitoring compliance with the law-abiding state in the public administration system, a special procedure for consideration and resolution of administrative and legal disputes arising from managerial relations. Administrative justice is aimed at ensuring the adoption of legally sound, timely, fair and understandable decisions in cases concerning the rights of people. Administrative justice ensures the rights of citizens in the administrative process. Finally, administrative justice has a great impact on the quality of public services and fair treatment of citizens. The process of making administrative decisions, there is a balance between issues of efficiency, regularity and the mechanical application of existing rules. Of course, the improvement of any social system is a necessary and sufficient condition for the existence and functioning of the system by itself. In general, the entire justice system is increasingly revealing the failure of efforts to protect the law-abiding state on the previous regulatory and organizational basis, legislative acts adopted in recent years in the legal field.